Evaluating project decisions : case studies in software engineering - Hoover, Carol L., 1955- (Addison-Wesley, 2010)
"Using a real-world, case study approach, the authors show how to evaluate software project problems and situations more effectively, thoughtfully assess your alternatives, and improve the decisions you make. Drawing on their own extensive research and experience, the authors bridge software engineering theory and practice, offering guidance that is both well-grounded and actionable. They present dozens of detailed examples from both successful and unsuccessful projects, illustrating what to do and what not to do."--Jacket.